Analysis of super‐source‐follower‐based GHz‐bandwidth biquadratic low‐pass filters - Chen, Hsiao‐Chin; Yen, Ming‐Yu; Lin, Tzu‐Yu; Cheng, Kai‐Hsun (International journal of circuit theory and applications, 2024)
Summary The design of GHz‐bandwidth super‐source‐follower‐based low‐pass filters (SSF‐LPFs) is investigated. The transfer function is derived by considering transistor parasitics. The behaviors of SSF‐LPFs can be predicted accurately with these formulas. The theoretical values of pole/zero frequencies of the circuit agree well with the corresponding simulation results. Moreover, the relationship between the Q factor and the phase margin of the biquadratic filter is revealed. Two 1.3‐GHz 4th‐order LPFs are designed using 90‐nm CMOS technology, where one contains a high‐Q biquad with a small phase margin and a low‐Q biquad, while the other is built with two biquads with moderate Q factors and sufficient phase margins. For the former, the discrepancy between the theoretical and simulated phase margin is <2°, and the discrepancy between the theoretical and simulated corner frequency is <6%. For the latter, the discrepancy between the theoretical and simulated phase margin is <4°, and the discrepancy between the theoretical and simulated corner frequency is <4%. The filter containing biquads with sufficient phase margins is fabricated and occupies an area of 0.44 mm2. Consuming 14.4 mW, the filter delivers a bandwidth of 1.3 GHz, P1dB of −11.94 dBm, and IIP3 of −4.5 dBm. The relationship between the Q factor and the phase margin of the GHz‐bandwidth super‐source‐follower‐based low‐pass filters is revealed. A 4th‐order low‐pass filter is then implemented using 90‐nm CMOS technology, and the filter delivers a bandwidth of 1.3 GHz, P1dB of −11.94 dBm, and IIP3 of −4.5 dBm.